Farmers as co-developers and adopters of green-manure cover crops in West and Central Africa - Tarawali, G.; Douthwaite, Boru; Haan, Nicoline C. de; Tarawali, Shirley A. (CAB International, 2002)
This chapter refers to four technologies involving cover crops and integrated crop-livestock interventions developed under varying social, ecological and production systems, in which farmers and researchers, working in partnership to combine indigenous knowledge and circumstances with research interventions, have contributed to the Development of the final innovation. For each innovation, a brief account is given of the technical Development history and the lessons that have been earned through the interaction of researchers and farmers, together in some cases, with extension services. Experiences from these examples are pooled in the discussion to highlight the importance of partnerships in the Development of agricultural interventions suitable for small-scale farmers in sub-saharan Africa.